Low Subicular Volume as an Indicator of Dementia-Risk Susceptibility in Old Age - Kagerer, Sonja M.; Schroeder, Clemens; van Bergen, Jiri M. G.; Schreiner, Simon J.; Meyer, Rafael; Steininger, Stefanie C.; Vionnet, Laetitia; Gietl, Anton F.; Treyer, Valerie; Buck, Alfred; Pruessmann, Klaas P.; Hock, Christoph; et al. (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Hippocampal atrophy is an established Alzheimer's Disease (AD) biomarker. Volume loss in specific subregions as measurable with ultra-high field MRI may reflect earliest pathological alterations. METHODS: Data from PET for estimation of cortical amyloid β (Aβ) and high-resolution 7 Tesla T1 MRI for assessment of hippocampal subfield volumes were analyzed in 61 non-demented elderly individuals who were divided into risk-categories as defined by high levels of cortical Aβ and low performance in standardized episodic memory tasks. RESULTS: High cortical Aβ and low episodic memory interactively predicted subicular volume (F(3,57)=5.90, p=0.018). The combination of high cortical Aβ and low episodic memory was associated with significantly lower subicular volumes, when compared to participants with high episodic memory (p=0.004). DISCUSSION: Our results suggest that low subicular volume is linked to established indicators of AD risk, such as increased cortical Aβ and low episodic memory. Our data support subicular volume as a marker of dementia-risk susceptibility in old-aged non-demented persons.